Research on the trend of Yen exchange rate and international crude oil price fluctuation affected by Japan's earthquake - Xiaoguang Li; Menggang Li (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: Whether this earthquake would become a turning point of the high oil price and whether it would have big impact on yen exchange rate are two issues to be discussed in this paper. Design/methodology/approach: To analyze deeply the internal relations between changes in yen exchange rate caused by Japan's earthquake and price fluctuation of international crude oil, this research chooses middle rate of yen exchange rate during the 45 days around Japan's earthquake and price data of international crude oil to do an empirical study, uses VAR model and HP trend decomposition to estimate the mutual effect of yen exchange rate change and price fluctuation of international crude oil in this period. Findings: It has been found in the empirical study with VAR model and HP filter decomposition model on the yen exchange rate and the international crude oil price fluctuation during 45 days around Japan's earthquake that: the fluctuation of yen exchange rate around the earthquake is one of the main reasons for the drastic fluctuation of international crude oil price in that period. The fluctuation of international crude oil price directly triggered by yen exchange rate occupies 13.54% of its total variance. There is a long-term interactive relationship between yen exchange rate and international crude oil price. The upward trend of international crude oil price after the earthquake was obvious, while yen exchange rate remained relatively stable after the earthquake. Originality/value: As economic globalization goes deeper, the influence of natural disasters on international financial market and world economy will become more and more obvious. It has a great revelatory meaning to studying further each kind of natural disaster's impacts on international financial market and world economics.
Keywords: 650; yen exchange rate; international crude oil price; Japan's earthquake